2001
DOI: 10.1177/019251301022001002
|View full text |Cite
|
Sign up to set email alerts
|

Marital Disruption, Parental Investment, and Children's Academic Achievement

Abstract: Although previous research has noted the detrimental impact of parents' marital disruption on children's schooling, less is known about whether such detriments are observable prior to the disruption. Based on two waves of a nationally representative longitudinal data set, this study has found that even prior to family dissolution, both boys and girls from families that subsequently dissolve perform less well than their peers whose parents remain married. Families at the predisruption stage are also characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
3
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 43 publications
3
55
3
7
Order By: Relevance
“…En utilisant la même base de données que les auteurs précédents (Add Health), Brown (2006) conclut différemment, car elle trouve que la transition d'une famille mariée à une famille monoparentale n'est pas associée à une baisse du niveau d'engagement scolaire chez les adolescents durant la même année. Sun et Li (2001) (Harknett, 2009). Finalement, Cavanagh et Huston (2006) constatent que les enfants nés en union libre ont plus de troubles extériorisés (tel que l'agressivité) que les enfants nés dans le mariage, mais la rupture d'une union libre a un effet positif alors que le divorce a un effet négatif.…”
Section: Rupture D'un Mariageunclassified
See 2 more Smart Citations
“…En utilisant la même base de données que les auteurs précédents (Add Health), Brown (2006) conclut différemment, car elle trouve que la transition d'une famille mariée à une famille monoparentale n'est pas associée à une baisse du niveau d'engagement scolaire chez les adolescents durant la même année. Sun et Li (2001) (Harknett, 2009). Finalement, Cavanagh et Huston (2006) constatent que les enfants nés en union libre ont plus de troubles extériorisés (tel que l'agressivité) que les enfants nés dans le mariage, mais la rupture d'une union libre a un effet positif alors que le divorce a un effet négatif.…”
Section: Rupture D'un Mariageunclassified
“…Par contre, le rôle modérateur du genre dans la relation entre trajectoire familiale et rendement scolaire est rarement analysé. Les résultats montrent généralement que les garçons sont plus affectés que les filles par une séparation de leurs parents (Amato, 2000 ;Demo et Acock, 1988), mais certaines recherches révèlent une absence de différence entre les genres (Cooper et collab., 2011 ;Morrison et Cherlin, 1995 ;Sun et Li, 2001, ou encore l'existence d'un désavan-tage partiel pour les filles (Allison et Furstenberg, 1989). Le désavantage observé chez les garçons pourrait provenir du fait que la garde des enfants revient plus souvent à la mère qu'au père suite à une séparation.…”
Section: Différence Selon Le Genreunclassified
See 1 more Smart Citation
“…Research shows consistently that growing up in some non-traditional families may be associated with risky behaviors, which may in turn have negative consequences for subsequent life course. For example, children of divorced parents are shown to have poorer academic performance (Sun and Li, 2001;Steele et al, 2009), lower economic security (Biblarz and Gottainer, 2000), and earlier sexual activity and pregnancies (Kiernan and Hobcraft, 1997;Wu and Thomson, 2001) than children of intact families. Studies on the emotional status of children living in non-traditional families are few and far between, and even the few are focused on the children of mainly early and middle childhood (Kiernan and Mensah, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Divorce generally leads to a severe decline in the standard of living of single mother families, and this decline may increase children's developmental risk in various aspects including academic achievement. According to Sun (2001) and Sun and Li (2001), the economic hardship associated with divorced families was found to mediate the educational defects of children in such families. Conger et al (1992) in a study with a sample of European American two-parent families of adolescent boys, found that economic hardship were significantly related to parental depression which were correlated with disruptions in parenting behaviors such as parental involvement, parental warmth, and discipline.…”
mentioning
confidence: 99%